Scientific substantiation of improvement of the ecological-hygienic monitoring procedure of potable and natural waters quality - Zorina, O.V. (Environment & Health, 2018)
The study is aimed at scientific substantiation and improvement of parameters and criteria of the potable and natural waters quality monitoring in accordance with the requirements of the European legislation. Materials. The analysis was carried out of the European and Ukrainian regulatory documents regarding the potable and natural waters quality. The quality of potable tap water from surface and subsurface sources of drinking water supply, in the bottling places, and packaged was investigated for meeting sanitary-chemical indicators in different regions of Ukraine during the last 17 years (more than 600 samples). Methods: bibliographical, regulatory-searching, hygiene, sanitary-chemical, and expert evaluating. Main results. The work consist of the scientific substantiation, systematization, and improvement of parameters and criteria of potable and natural waters quality monitoring in accordance with the requirements of the European legislation and on the basis of longitudinal research of priority indicators of the potable and natural waters quality, as well as the potable water influence on the consumer health. It is noted that the development of the program for monitoring the drinking water should be conducted taking into account the results of monitoring of natural waters. Improved analysis criteria that should be conducted in case of water monitoring development, it is proposed to analyze the presence of problem indicators, which concentration was unstable and exceeded 75% of the norm, as well as before cleaning exceeded the hygienic norm for drinking water. The comparative assessment of Directive 98/83/EC and ДСанПіН 2.2.4-171-10 concerning the procedure for monitoring the quality of drinking water by microbiological and organoleptic indicators showed that at the productivity of the water supply system up to 130 000 m3/day in the ДСанПіН the stricter control is regulated, which requires preservation in in case of implementation of the said directive. It has been found that Directive 98/83/EC does not have a procedure for monitoring the quality of drinking water in relation to the content of residual quantities of reagents and the hygiene standard for them (regulated in ДСанПіН 2.2.4-171-10), which needs to be preserved in the revised national regulatory document. We have found that refined drinking water of superficial sources of drinking water supply has a stable composition. Requirements for the quality of such waters and periodicity of their quality control are determined (coincide with the requirements for underground drinking water). The periodicity of mineral substances determination in potable water with artificial mineralization in potable water was reduced in bottling places with productivity less than 5m3/day in order to prevent the production and sales of the desalinated water (earlier – one time a week, now – one time per month). The standard for chlorates was established according to the WHO (0,7 mg/l) recommendations and the periodicity of the chlorates level control was set (one time per month in case of potable water disinfection with the chloride dioxide); stricter control of potable water quality was set for the content of trihalomethanes (in case of minimization of their content-at least on time per three months). It was pointed for the first time that after the water supply systems refurbishment and changes in the water treatment technology the manufacturers can carry out the potable water quality control not of a full list of the indicators, but only for those that can be changed, what is cost-effective. It was determined that there is a need in implementation of complex ecological hygienic monitoring of natural and potable waters as of today, what will be a significant step in improvement of the potable waters quality and European legislation implementation in Ukraine.